FACTORS INFLUENCING CUSTOMER EXPERIENCE WHEN USING ANTHROPOMORPHIC GENERATIVE AI CHATBOTS: A PERSPECTIVE ON LANGUAGE STYLE AND RECOMMENDATIONS - Aisyah Apriliana Putri; Jaka Nugraha (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of anthropomorphic Generative AI chatbots on customer experience through the perspectives of language style and recommendations. The research method used is a quantitative approach with a survey technique. The research sample consists of students from the Office Administration Education Study Program at Surabaya State University from the 2022-2024 batch who have used Generative AI chatbots. Data analysis was conducted using Structural Equation Modeling–Generalized Structured Component Analysis (SEM-GSCA). The results of the study indicate that anthropomorphic Generative AI chatbots have a significant effect on language style and recommendations, as well as a positive effect on customer experience. In addition, language style and recommendations were also found to have a significant effect on customer experience.